Cryopreservation of Aceh Cattle Semen with Date (Phoenix dactylifera) Extract Supplementation - Dwitya, Yonadiah; Eriani, Kartini; Saputra, Hendra; Al-Azhar, Al-Azhar; Rizal, Muhammad (Biosaintifika: Journal of Biology & Biology Education, 2019)
Cryopreservation process could affect spermatozoa quality during from reactive oxygen species (ROS) produced in cellular metabolism and the environment. Spermatozoa damage caused by ROS during cryopreservation can be reduced with the addition of natural antioxidant which commonly found in fruits like date palm. This research was done to investigate the influence of date extract on semen quality after cryopreservation. This experimental study used a completely randomized design with 4 treatments and 6 replications. Semen collected from two aceh cattle bulls was diluted in tris egg yolk extender contained different concentrations (v/v) of date extract: 0% (P0, control), 0.75% (P1), 1% (P2), and 1.25% (P3) before cryopreserved at -196 ºC for 7 days. Semen quality prior to and after cryopreservation as well as sperm DNA integrity were determined by standard microscopic and laddering methods, respectively. The results showed that the addition of 1% date extract could maintain viability (68.67%), plasma membrane integrity (62.33%), and abnormality (18.58%) of aceh cattle spermatozoa, but unable to maintain its motility above 40%. There was no DNA fragmentation observed in both treated and fresh semen. This is the first study investigates the influence of supplementation of date palm extract on preserved aceh cattle spermatozoa diluted in egg yolk tris based extender.